ABNORMALITIES IN THE VERTEBRAL COLUMN OF INDIAN MACKEREL - Kulkarni, G M (Indian Journal of Fisheries, 2011)
Some abnormalities notiosd In the constituents of the vertebral columnsof 9 specimens of mackerel are reported. These include ossified haemal bracesfarming plate-like structures, fused as well as closely apposed vertebrae, b'fidhaemal spine, super-numerary neural and haemal arches and spines, absence ofneural spine and fused proximal halves of neural spines which distally remainseparate